(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
India has a vast population of 1.3 Billion people out of which approximately 44% have a health insurance policy 1. In the FY 2017-18 alone, there were approximately 4.7 million Indians who claimed mediclaim insurance for hospitalization done which included both pre-planned as well as emergency visits to the hospital 2. Each of these claims took around 4-6 hours of processing and follow-up time costing hugely to the claimants 3. The objective of this paper is to evaluate the reduction in Turn Around Time (TAT) and thereby reduce costs in terms of man-hours saved by effective use of Blockchain for the purpose of settling claims.